Career escalation training. Five-year follow-up. - Sainer, E A (1975)
A study has been reported on 5 years of experience in a community mental health center with a career escalation training program for indigenous workers in a ghetto community. More than one-half entered the program during the 5-year period and about one-third had either achieved a degree or were still active in the Program at the time of this study. Although it is too early to assess the full impact of the program on career advancement, the authors believe that at least a master's degree is required for true upward and lateral mobility. The most striking finding was the high retention rate in the mental health field of those workers who entered the program in contrast to those who didn't. A number of suggestions have been made to improve the effectiveness of a career escalation training program. It is too early to tell whether the long term benefits for individuals, the Center, and the mental health field at large justify the cost and the continuation of such educational release time programs.